2019
DOI: 10.1590/1980-57642018dn13-010006
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in conversational discourse abilities A comparative study

Abstract: ABSTRACT. Conversational discourse (CD) is among the most complex tasks in everyday life and relies on multiple cognitive domains (communicative and executive abilities). Alterations in discourse comprehension and production are often present in pathological aging. However, there is still a need to identify changes in healthy aging. Objective: This study aimed to compare young and older adults for the frequency of impaired communicative behaviors on a CD task. Performance was scored according to the Complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 72 publications
2
4
0
3
Order By: Relevance
“…This outcome is in line with the result obtained by Daniluk and Borkowska [ 17 ] but in contrast with other studies where an age-related decline was detected [ 88 , 89 ]. In a study by Pereira and collaborators [ 90 ], the conversational discourse of a group of older individuals (70 years old) was transcribed, analysed and compared to the transcription of conversational samples of a group of young adults (27 years old). The results highlighted the difficulty of older adults to respect turn taking, to maintain the topic of the conversation and to return to the original topic after a thematic shift.…”
Section: Discussionmentioning
confidence: 99%
“…This outcome is in line with the result obtained by Daniluk and Borkowska [ 17 ] but in contrast with other studies where an age-related decline was detected [ 88 , 89 ]. In a study by Pereira and collaborators [ 90 ], the conversational discourse of a group of older individuals (70 years old) was transcribed, analysed and compared to the transcription of conversational samples of a group of young adults (27 years old). The results highlighted the difficulty of older adults to respect turn taking, to maintain the topic of the conversation and to return to the original topic after a thematic shift.…”
Section: Discussionmentioning
confidence: 99%
“…The more coherent a discourse, the more that the speaker is maintaining a theme of conversation and the more likely that the listener will be able to understand the meaning intended by the speaker. Although younger and older adults are remarkably similar in a variety of conversational discourse abilities (Pereira et al, 2019), older adults have been found to produce less globally coherent discourse, especially when recounting personal experiences (Pereira et al, 2019;Wright et al, 2014). If the speech of older adults includes more tangential asides and is less globally coherent, it may be more difficult for a listener to actively predict upcoming information in the discourse.…”
Section: Predictability and Discourse Coherencementioning
confidence: 99%
“…Dos 19 artigos que compõem esta revisão, seis deles investigaram o efeito da escolaridade (JERÔNIMO, 2018;MACKENZIE et al, 2007;ZANINI et al, 2005;MACKENZIE, 2000;DORZE;BÈDARD, 1998;JUNCOS-RABADÀN, 1996); o restante dos artigos não incluiu tal variável em seus experimentos; nenhum estudo investigou o efeito dos hábitos de leitura e escrita. É interessante salientar que dois estudos utilizaram amostras de populações brasileiras (PEREIRA et al, 2019;JERÔNIMO, 2018). Do total de artigos selecionados, 18 foram publicados em inglês e um em português.…”
Section: R E S U L T a D O Sunclassified
“…Todos os artigos apresentaram uma abordagem quantitativa, sendo os objetivos, em geral, bastante heterogêneos. Alguns estudos focalizaram aspectos microestruturais do discurso (CAPILOUTO; WRIGHT; MADDY, 2016), como coerência local e informatividade (JUNCOS-RABADÁN; PEREIRO; RODRÍGUEZ, 2005), diversidade lexical e conteúdo léxico-semântico (DORZE; BÉDARD, 1998) e coesão (SHERRATT; BRYAN, 2019; BABAEI; GHAYOUMI--ANARAKI; MAHMOODI-BAKHTIARI, 2019; SALING; LAROO; SALING, 2012) etc., enquanto outros focalizaram aspectos macroestruturais, como coerência global e suas relações com processos cognitivos (PISTONO et al, 2017;CANNIZZARO;COELHO, 2013;WHITWORTH et al, 2015;CAPILOUTO, 2009;JAMES et al, 1998), ou, ainda, ambas as dimensões discursivas (macro e microestruturais) (PEREIRA et al, 2019;MARINI et al, 2005;JUNCOS-RABADÁN, 1996;GLOSSER;DESER, 1992).…”
Section: R E S U L T a D O Sunclassified
See 1 more Smart Citation